PENERAPAN UNSUR BUDAYA LOKAL DI AMBON SEBAGAI PENGEMBANGAN MOTIF DESAIN SANDAL - Hendro Aryanto; Nova Kristiana (Jurnal Dimensi DKV Seni Rupa dan Desain, 2016)
AbstractThe development of the slipper’s motive design begins with the analysis of the needs and problems which started to emerge on the slipper’s craftsmen’s business as the demand is decreasing due to thelack of the slipper’s motive design’s variation which is sold to Ambon. By applying the two local culture’s element which is Batik Beta and Parang Salawaku‘s motive on the slipper’sdesign, it is later expected to help to increase the sales. Beside it is used in daily life it is also used as souvenir for the tourist who’s visiting Ambon which eventually will also help to improve the prosperity and drive the economic life of the local community as well as the local government.AbstrakPengembangan motif desain sandal diawali dengan analisis kebutuhan dan masalah yang mulai muncul di usaha kerajinan sandal di mana permintaan yang menurun karena minimnya varian model motif sandal yang dijual ke Ambon. Dengan menerapkan dua unsur budaya lokal di Ambon yaitu motifBatik Beta dan Parang Salawaku pada desain sandal, nantinya diharapkan dapat meningkatkan penjualan. Selain dipakai juga dibuat sebagai souvenir bagi wisatawan yang sedang berkunjung di kota Ambon sehingga diharapkan dapat meningkatkan kesejahteraan serta perekonomian masyarakat setempat maupun pemerintah daerah.